COMPARISON OF TAX AMNESTY IMPLEMENTATION IN DEVELOPING COUNTRIES: Comparison Study of Tax Amnesty Implementation between Indonesia and India 2016 - Norbertus Purnomolastu (Politeknik Ubaya, 2017)
Taxes are a major source of revenue in a large states so the governer strives invarious ways to increase state revenues from taxes. This happened because noteveryone who pays taxes, referred as taxpayers is willing to pay their taxes welland correctly. One of the ways used by the government is issuing a policy thatcan increase tax revenues. That policy is known as Tax Amnesty.There are manycountries, both developed and developing countries that have implemented TaxAmnesty policy. In this paper, the author analyzes the implementation of TaxAmnesty by comparing two developing countries in Asia, Indonesia and India,This kind of study is known as comparative study. One of the considerations aboutthe pointing of the countries as subjects is both of Indonesia and India started toimplementing Tax Amnesty at the same time in 2016. The analysis is done bycomparing the background, the purpose of the implementation, and the resultsobtained from Tax Amnesty policy. The result of Tax Amnesty showed that differentimplementation purpose, implementation period, and the way to implementcaused different results of tax revenues.